Brain to Mind: Creation of the Virtual World - Mukundan, C. R.; Kamarajan, C. (Advances in Social Sciences Research Journal, 2021)
The human brain has developed the capability for routine sensory-motor monitoring and controls, present in all living beings, and additional skills for symbolic and verbal expressions of all sensory-motor activities and emotional experiences. Each brain could monitor and become aware of its own thoughts and emotions, all of which constitute the “mind”. Each person mentally creates verbal and symbolic expressions related to all sensory-motor activities and emotional experiences, and what one proposes to carry out. Each human being mentally creates an immensely enriched virtual mental world, and they succeed in physically realizing most of them. Different parts of the human brain contribute to different types of processing of incoming signals and retrieved signals already stored in the brain and the newly created and modified ideas are stored and used by the individual. The ideas and signals stored create emotional arousal, which the individual may experience and may make use of while dealing with the world and the individuals and other items of the which the individual may encounter in life. The ideas created within the brain may be played repeatedly and when the individual listens to his/her own ideas, the person becomes aware of the ideas. Normally awareness develops during the creation of new ideas, and during their retrieval. Oneself becoming aware or conscious of own ideas and the ideas expressed by others could develop an extensive knowledge base and may help in all planning and action executions, with others and materials of the world that one may encounter face to face or during their retrieval periods. The knowledge base has helped man to enhance the same, as well as, create new entities, which has been a routine human contribution during each person’s life. The emotions aroused during such interactions with the persons who may present ideas or own retrieved ideas are experienced by the self, who may express the emotionally loaded words or actions to others. The mind decides the world one lives in and mentally shares the realities one faces during one’s life period. Living is the process when one could share the same realities and the world, and could have experiences of the same and express own emotional reactions towards those realities.